PHYSICOCHEMICAL CHARACTERISTICS IN DIFFERENT DEGREES OF MATURATION OF THE FRUITS OF THREE PROMISING LINES OF PIÑÓN AND QUALITY OF OIL EXTRACTION FROM SEEDS - Gallo-Sevillano, Gabriela (2020)
In this work, the behavior and physicochemical characteristics of fruits, seeds, and the oil extracted from three promising sprocket lines CP041, CP052, and CP054 with degrees of maturation were evaluated: light green, yellow, yellowish-brown, and dark brown. Th e samples were obtained from the germplasm bank of the Portoviejo Experimental Station of the National Institute for Agricultural Research (INIAP-EEP), Manabí, Ecuador. In the statistical analysis, it was determined that the ripe fruits were the ones that presented the highest percentage of oil content, being the line CP041 the one that presented the highest content. In the percentage of seeds in nuts, the CP041 line had a higher yield than the CP054 line. As for proteins, the CP041 line stood out, in the percentage of fi ber and humidity CP052 and the percentage of ash CP054. In line CP041, the light green fruit oil had a higher iodine index and a saponifi cation index. Th e kinematic viscosity in the yellow fruit was the most outstanding with the other degrees of ripening. Th e yellowish-brown fruits presented the lowest acidity index. When the fruits studied were dark browns, there was a lower peroxide index and a lower range relative density. Th e fruits with the highest content of double bonds referring to the Iodo index were light green fruits in line CP052, while in line CP054 they were dark brown fruits. Th e dried fruits (dark brown) of the line CP052 and CP054 reached a high saponifi cation index in relation to the other degrees of ripeness. Th e values shown in the kinematic viscosity in the yellowish-brown fruits stand out from the other ripening stages in both the CP052 and CP054 lines. In relative density, both in lines CP052 and CP054, the yellow-green fruits stand out in relation to the other ripening stages.